Pengembangan Materi Pembelajaran Pendidikan Kewarganegaraan Tingkat Sekolah Menengah Atas Dalam Perspektif Islamisasi Ilmu Dan Pembinaan Akhlak Mulia - Surahman, Endang; Husaini, Adian; Mujahidin, Endin; Saefuddin, Didin (Ta'dibuna: Jurnal Pendidikan Islam, 2014)
Among the goals of Indonesian national education mentioned in Article 3 of Chapter 2 of the Indonesian Act No. 20 issued in 2003 is the development of students’ potentials to be deeply believing, cautiously devout and morally well-behaved individuals. This goal is considered quite religious, encouraging efforts to build a believing, devout and well-behaved nation. However, this very religious national education goal has in practice not yet been much achieved, since there are still many instances of prevalent moral violation in society, such as mass fighting, crimes, coercion, etc, in addition to horizontal conflicts among different political groups, ethnics, religious groups and others. In such situation, a thorough study on both the concept and implementation of the national education related to how it can build students’ good character is justified. This study takes a closer look at education in senior high schools as a case. This study seeks to: (1) point out some existing weaknesses of Citizenship Education subject matters taught in the first level of senior high schools, noticing the absence of Islamic values, (2) develop a model of revised subject matters of Citizenship Education for the first level of senior high schools through the perspectives of the Islamization of sciencesand good character building. This study takes a more descriptive approach in which all relevant things are explored and described. With this approach, this study describes a situation going on when the research is conducted, and analyzes the causes of a certain phenomenon found. In addition, this study uses content analysis to find out the extent to which character building is contained in textbooks. This study finds that: (1) the subject matters of Citizenship Education are in general empty from religious values in striking contrast with the religious nature of national education aim; (2) there is an urgent need for developing Citizenship Education subject matters based on the perspective of the Islamization of sciences that might better build high school students’ good character. Keywords: Akhlak Mulia, Islamisasi Ilmu, Pendidikan Kewarganegaraan,